Lesson Preparation Practices of Pre-service High School Science Teachers: Implications to Science Education - Yacap, Marites J. (Future Science / FSH-PH Publications, 2022)
Teacher preparation is a vital factor in the development of effective future teachers. As such, this study tried to determine the pre-service teachers’ lesson preparation practices in one of the Teacher Education Institutions in the Philippines and provided descriptions of their practice teaching experiences particularly on lesson planning/preparation. Quantitative and qualitative methods of research were used wherein data were gathered through questionnaires, documentary analysis and semi-structured interviews. Results revealed that the pre-service science teachers followed the systematic method of lesson preparation with the use of detailed lesson plans. Their lesson preparation practices are good and they are already prepared to face and hurdle the task of a real classroom teacher. Despite these, there are still aspects in lesson preparation that needs to be further developed like the formulation of affective domain objectives as well as the selection of appropriate motivational and assessment techniques. To further develop the pre-service program for science education, the study recommends that Teacher Education Institutions continue to design programs and activities regarding pre-service teachers’ development not only in science but also in other subject areas to enhance their lesson planning skills.